2012
DOI: 10.1007/s11999-012-2453-x
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal Chondral Defects Associated with Femoroacetabular Impingement

Abstract: Background Cam-type, pincer, and mixed femoroacetabular impingement (FAI) are accepted causes of labral and acetabular rim injury; however, the abnormal contact stresses associated with motion may damage other areas of the hip. Although cartilage damage to the femoral head has been reported previously in athletes, FAI-associated focal parafoveal chondral defects differ from previously reported lesions and represent a rare manifestation of the complex pathomechanics associated with FAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 20 publications
4
36
1
Order By: Relevance
“…We reasoned it might be useful for treating larger cartilage lesions ([ 2 cm 2 ) in the hip and began using the technique in 2009. In another report [66], the potential etiology of the rare parafoveal femoral head lesions seen in three of our six patients was described in more detail.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…We reasoned it might be useful for treating larger cartilage lesions ([ 2 cm 2 ) in the hip and began using the technique in 2009. In another report [66], the potential etiology of the rare parafoveal femoral head lesions seen in three of our six patients was described in more detail.…”
Section: Introductionmentioning
confidence: 69%
“…Three of these six patients were also included in a report describing the etiology of the parafoveal femoral head chondral defect [66]. At the request of that journal's editors, the details of treatment and Tegner and Lysholm outcome scores at 1 year were included in that report although the purpose of the report was to describe the chondral lesion.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, AMIC does not require complex cell expansion techniques. Other than comparative studies with microfracture [24,25] or MACI [28] described above, Leunig et al [30] reported six patients with AMIC using surgical dislocation of the hip. No complications occurred, and good post-operative outcome scores were reported.…”
Section: Autologous Matrix-induced Chondrogenesismentioning
confidence: 99%
“…At an average follow-up of 17 months, 19 of the 20 patients had a mean fill of 96% with macroscopically good quality repair tissue. Zaltz and Leunig [24] reviewed ten patients with symptomatic FAI diagnosed with parafoveal chondral defects confirmed at the time of surgical dislocation. Seven of the ten patients were treated by microfracture (other 3 were treated by AMIC), and all the patients were able to return to their pre-operative level of function with the exception of one patient who had a problem in the contralateral hip.…”
mentioning
confidence: 99%
“…Indeed, reconstruction of the femoral head with osteochondral autograft transfer system (OATS) via hip dislocation is a promising and novel alternative in the treatment of chondral defects of the hip. [2] However, the etiology of the osteochondral defects of the hip joint is extremely complicated and the relationship between FAI and osteochondral lesions of the femoral head has not yet been adequately studied in the literature. [3][4][5][6] Herein, we aim to demonstrate that a combination of OATS…”
mentioning
confidence: 99%